2013
DOI: 10.1007/s00253-013-4693-4
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a glutaminase enzyme accounting for the majority of glutaminase activity in Aspergillus sojae under solid-state culture

Abstract: Glutaminase, an enzyme that hydrolyzes L-glutamine to L-glutamate, plays an important role in the production of fermented foods by enhancing the umami taste. In this study, we found ten glutaminase genes in the Aspergillus sojae genome by conducting a BLAST search of the characterized glutaminase sequence. We subsequently constructed glutaminase gene disruptants. The glutaminase activity of the gahB disruptant was decreased by approximately 90 % in A. sojae and Aspergillus oryzae, indicating that this enzyme (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…We found that the glutaminase activity of the gahB disruptant decreased by approximately 90% as compared to the control strain. 16) To determine which glutaminase gene product contributes to glutamate production in soy sauce fermentation, we prepared soy sauces using single disruptants of the 10 glutaminase genes in A. sojae. It is known that the glutamate concentration in soy sauce correlates positively with the glutaminase activity of koji molds.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We found that the glutaminase activity of the gahB disruptant decreased by approximately 90% as compared to the control strain. 16) To determine which glutaminase gene product contributes to glutamate production in soy sauce fermentation, we prepared soy sauces using single disruptants of the 10 glutaminase genes in A. sojae. It is known that the glutamate concentration in soy sauce correlates positively with the glutaminase activity of koji molds.…”
Section: Resultsmentioning
confidence: 99%
“…The cell wall-bound and total glutaminase activities of the glutaminase gene disruptants were measured as previously described. 15,16) The glutaminase activities of KGd-T124, KGd-Tall10, and KGd-NT124-4 were very low, and were hence measured by increasing the reaction time.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations